Constitutional Duties of the Man and the Citizen in the Focus of Doctrine - MARKHGEYM, MARINA V.; TSALIEV, ALEXANDER M.; KEMRYUGOV, TENGIS KH. (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The aim of this article is to present the results of a number of doctrinal perspectives of the study of the constitutional duties of man and citizen which determined general and special approaches to the interpretation of constitutional duties; their author interpretation is proposed. The duties of a citizen arise from the relation of an individual in a state. Citizens, unlike other persons residing in the state territory, are affected not only by the territorial supremacy of the state, but also by their personal supremacy. It applies to citizens when they are outside the territory of their state. RESUMEN El objetivo de este artículo es presentar los resultados de una serie de perspectivas doctrinales del estudio de los deberes constitucionales del hombre y el ciudadano que determinaron enfoques generales y especiales para la interpretación de los deberes constitucionales; se propone la interpretación de su autor. Los deberes de un ciudadano surgen de la relación de un individuo en un estado. Los ciudadanos, a diferencia de otras personas que residen en el territorio estatal, se ven afectados no solo por la supremacía territorial del estado, sino también por su supremacía personal. Se aplica a los ciudadanos cuando se encuentran fuera del territorio de su estado.